2023
DOI: 10.1073/pnas.2303675120
|View full text |Cite
|
Sign up to set email alerts
|

AcrIIC4 inhibits type II-C Cas9 by preventing R-loop formation

Abstract: Anti-CRISPR (Acr) proteins are encoded by phages and other mobile genetic elements and inhibit host CRISPR-Cas immunity using versatile strategies. AcrIIC4 is a broad-spectrum Acr that inhibits the type II-C CRISPR-Cas9 system in several species by an unknown mechanism. Here, we determined a series of structures of Haemophilus parainfluenzae Cas9 (HpaCas9)-sgRNA in complex with AcrIIC4 and/or target DNA, as well as the crystal structure of AcrIIC4 alone. We found that AcrIIC4 resides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Similar to the structure by Hwang et al, Sun et al report an elongated homodimeric AcrIIC4 conformation in the absence of HpaCas9. However, it is shown that soluble AcrIIC4 is monomeric and when bound to HpaCas9 monomeric AcrIIC4 assumes the more compact conformation similar to the conformation observed by Kim et al Explaining the ambiguity in the previously reported structural conformations, Sun et al reveal that the long central alpha helix in the elongated structure of AcrIIC4 bends to facilitate AcrIIC4 interactions with HpaCas9 ( 10 ).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Similar to the structure by Hwang et al, Sun et al report an elongated homodimeric AcrIIC4 conformation in the absence of HpaCas9. However, it is shown that soluble AcrIIC4 is monomeric and when bound to HpaCas9 monomeric AcrIIC4 assumes the more compact conformation similar to the conformation observed by Kim et al Explaining the ambiguity in the previously reported structural conformations, Sun et al reveal that the long central alpha helix in the elongated structure of AcrIIC4 bends to facilitate AcrIIC4 interactions with HpaCas9 ( 10 ).…”
mentioning
confidence: 82%
“…Furthermore, Acrs can be repurposed for controlling Cas protein activity in genome editing or other biotechnological applications ( 9 ). In this issue of PNAS, Sun et al have studied structures of Cas9 bound to Acr protein AcrIIC4 and thereby uncovered a novel mechanism of Cas9 inhibition: preventing complete R-loop formation ( 10 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, phages have evolved anti-CRISPR proteins (Acrs) that inhibit the cleavage of Cas proteins. For example, AcrIIC4 is a broad-spectrum Acr that binds between the two recognition domains of Cas9, REC1 and REC2, restricting the movement of the REC2 domain and thereby maintaining the integrity of its genome (Sun et al 2023b ). Previous studies have demonstrated that phage–bacteria coevolution follows fluctuating selection in the soil microcosms, where phages and bacteria adapt to their contemporary counterparts in time (Gomez and Buckling 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acrs are versatile inhibitors that are typically small and exhibit low homology to other known protein families in both their protein sequences and three-dimensional structures 7 , 8 . Acrs subvert CRISPR-systems through various strategies, including promoting Cas protein degradation 9 , blocking crRNA loading 10 , 11 , preventing DNA recognition 12 15 , and obstructing the activation of the Cas protein by preventing the conformational changes of the surveillance complex 16 19 .…”
Section: Introductionmentioning
confidence: 99%